2022
DOI: 10.1161/jaha.121.022852
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Ceramide Levels Are Elevated in Patients With Early Coronary Atherosclerosis and Endothelial Dysfunction

Abstract: Background Elevated plasma ceramides are independent predictors of cardiovascular disease and mortality in patients with advanced epicardial coronary artery disease. Our understanding of plasma ceramides in early epicardial coronary artery disease, however, remains limited. We examined the role of plasma ceramides in early coronary atherosclerosis characterized by coronary endothelial dysfunction. Methods and Results Participants presenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 54 publications
(79 reference statements)
0
14
1
Order By: Relevance
“…The study protocol has been described in detail elsewhere. 8,16–18 Patients presenting to the catheterization laboratory with nonobstructive coronary artery (<40% angiographic stenosis in major vessels) underwent invasive coronary functional testing using an intracoronary Doppler guidewire. A Doppler guidewire (0.014-inch FloWire; Philips/Volcano, Inc) was advanced 2 to 3 mm distal to the tip of 2.2F coronary infusion catheter (Ultrafuse; SciMed Life System) positioned into the mid-portion of the left anterior descending artery.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The study protocol has been described in detail elsewhere. 8,16–18 Patients presenting to the catheterization laboratory with nonobstructive coronary artery (<40% angiographic stenosis in major vessels) underwent invasive coronary functional testing using an intracoronary Doppler guidewire. A Doppler guidewire (0.014-inch FloWire; Philips/Volcano, Inc) was advanced 2 to 3 mm distal to the tip of 2.2F coronary infusion catheter (Ultrafuse; SciMed Life System) positioned into the mid-portion of the left anterior descending artery.…”
Section: Methodsmentioning
confidence: 99%
“…CFR ≤2 was consistent with a clinical diagnosis of CMD associated with cardiovascular disease and MACE as described previously. 8,13,18–20…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Exogenous c16 ceramide-mediated endothelial NO synthase (NOS) uncoupling and dysregulated protein phosphatase 2 (PP2A) were found to damage human aortic endothelial cells in a study of atherosclerotic patients (70). Another study in patients with coronary arteries also found that ceramides were associated with coronary endothelial dysfunction (71). However, more mechanistic studies are needed to confirm the findings.…”
Section: Ceramides and Vesselsmentioning
confidence: 99%
“…Sphingolipids are bioactive lipids found in atherosclerotic plaques, which have been linked to both the development and progression of atherosclerosis. Although their specific effects in human atherosclerotic plaques are still unclear, ceramides are an important component in sphingolipids that are also associated with atherosclerosis ( 71 ). By promoting their aggregation through ceramide-ceramide interactions, SM may be converted to ceramides by aSMase on low-density lipoprotein (LDL) surfaces, thus accelerating the onset of atherosclerosis.…”
Section: Ceramides and Atherosclerosismentioning
confidence: 99%